(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
Psychological and behavioural symptoms in Alzheimer’s disease are the essential causes of the depletion of caregivers and the source of suffering and impairment of the quality of life of the patient. Psychological and behavioural symptoms include depression which is also one of the most serious complications associated with Alzheimer’s disease. In our study focused on the ’depressive manifestations in patients suffering from Alzheimer’s disease’, the objective is to bring a better knowledge on Alzheimer’s disease, recognize, describe depressive manifestations in patients and evaluate search psychological and behavioural symptoms most associated with depression in Alzheimer’s disease. Key words: Alzheimer disease, behavioural symptoms, depressive manifestations